Relationship between Family Social Support and Quality of Life for Hypertensive Elderly in Tenggela Village, Tilango District - Mike Susianti; Rini Asnawati; Sintia Karim Polapa (PSPP JOURNALS, 2022)
The elderly have problems related to aspects of decreased physical function, namely a decrease in body systems and a decrease in the ability of the five senses that affect activities. The decrease in the physical condition of the elderly causes a decrease in the efficiency of cardiovascular homeostatic mechanisms, including hypertension. The design of this study used an analytic survey with a cross sectional approach, sampling using total sampling, obtained 58 respondents, then given a questionnaire. The results showed that the p value was 0.001 (p <0.05), which means that there is a significant effect. It can be concluded that there is a relationship between family social support and the quality of life of the elderly with hypertension. So it is hoped that the increase in family social support for the elderly so that they are able to face a happy and optimistic old age.